From document to history : epigraphic insights into the Greco-Roman world - Noreña, Carlos F.,; Papazarkadas, Nikolaos, 1974- (Brill Studies in Greek and Roman Epigraphy, 2019)
In From Document to History: Epigraphic Insights into the Greco-Roman World , editors Carlos Noreña and Nikolaos Papazarkadas gather together an exciting set of original studies on Greek and Roman epigraphy, first presented at the Second North American Congress of Greek and Latin Epigraphy (Berkeley 2016). Chapters range chronologically from the sixth century BCE to the fifth century CE, and geographically from Egypt and Asia Minor to the west European continent and British isles. Key themes include Greek and Roman epigraphies of time, space, and public display, with texts featuring individuals and social groups ranging from Roman emperors, imperial elites, and artists to gladiators, immigrants, laborers, and slaves. Several papers highlight the new technologies that are transforming our understanding of ancient inscriptions, and a number of major new texts are published here for the first time.